2022
DOI: 10.1002/pmic.202200081
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics reveals MRPL4 as a high‐risk factor and a potential diagnostic biomarker for prostate cancer

Abstract: Through digital rectal examinations (DRE) and routine prostate-specific antigen (PSA) screening, early prostate cancer (PC) treatment has become possible. However, PC is a complex and heterogeneous disease. In vivo, cancer cells can invade adjacent tissues and metastasize to other tissues resulting in hard cures. Therefore, the key to improving PC patients' survival time is preventing cancer cells' metastasis. We used mass spectrometry to profile primary PC in patients with versus without metastatic PC. We nam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…MRPL4 has been identified as a high-risk factor for prostate cancer (PC) and a potential diagnostic biomarker. 39 Additionally, MRPS12 has been implicated in ovarian cancer. 40 Several reports indicate that POLR2L plays a significant role in PC, glioblastoma (GBM), and HBV-related hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
“…MRPL4 has been identified as a high-risk factor for prostate cancer (PC) and a potential diagnostic biomarker. 39 Additionally, MRPS12 has been implicated in ovarian cancer. 40 Several reports indicate that POLR2L plays a significant role in PC, glioblastoma (GBM), and HBV-related hepatocellular carcinoma (HCC).…”
Section: Discussionmentioning
confidence: 99%
“…As prostate cancer progresses to an advanced stage of metastasis, there is a more substantial alteration in the proteomic changes reflecting cell cycle and DNA damage [ 13 , 14 ]. Several studies have identified protein markers that promote prostate cancer metastasis using proteomics techniques [ 15 , 16 ]. However, molecular markers that accurately predict metastatic risk are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Deep mining of the cancer proteome could help to understand the mechanism of tumorigenesis and discover novel biomarkers or potential therapeutic targets. In PCa, proteomics was applied to discover biomarkers [ 4 6 ], key proteins in PCa progression [ 7 , 8 ], or protein interaction networks [ 9 , 10 ]. In recent years, the application of 4-dimensional proteomics has provided a promising tool to identify more proteins with lower abundance due to its high sensitivity, compared with traditional 3D proteomics [ 11 ].…”
Section: Introductionmentioning
confidence: 99%